LNG Cold Energy Use in the Puerto Bravo Thermoelectric Power Plant (LACCEI, 2024)
Natural gas can be transported as liquefied natural gas to the final consumption points when pipelines are not feasible, however, this industry faces new challenges as it is increasingly used in the market. One of its main challenges focuses on the use of the cold energy available at the time of its regasification, so as not to discard it into the environment or the seawater. It is possible to use cold energy in a natural gas power generation plant, using it to capture the carbon dioxide generated after combustion. There is a novel process to capture CO2 in a solid phase that uses less equipment and generates a lower penalty in energy efficiency compared to processes based on CO2 absorption with amines. This novel process could be used in the Puerto Bravo thermoelectric plant, located in Arequipa, Peru, which operates with B5 Diesel due to the paralysis of the South Peruvian Gas Pipeline project and can be supplied with liquefied natural gas in the coming years. Therefore, this work aims to model the process of carbon capture and storage in a solid phase, previously replacing B5 Diesel with natural gas. In the simulation, the steam cycle was included for better utilization of the combustion gas energy resulting in a net power of 225 MW and a capture of 94% of the CO2 generated from natural gas combustion. Finally, the penalty on the energy efficiency of the cycle was 4.87%, where only 11.5 MW of power was used in the process of carbon capture and storage.